1988
DOI: 10.1097/00006254-198843030-00012
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Acid-Base State and Apgar Score in Term Breech Neonates

Abstract: Umbilical cord acid-base state and Apgar score were compared in neonates after breech and vertex term birth. The breech group comprised 149 consecutive newborns, 91 born vaginally and 58 by cesarean section. The control group consisted of a random sample of 150 newborns in vertex presentation: 100 born vaginally and 50 by cesarean section. Among vaginally born babies, the 1-min Apgar score was more often depressed in the breech presentation group than in the vertex group; after 5 min the Apgar scores were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This is probably a misconception. Luterkort and Marsál have examined this issue and compared the outcome for breech babies, not only within groups of mode of delivery, but also between groups of fetal presentation [2]. Indeed, when looking at breech babies delivered vaginally versus those delivered abdominally, pH levels were lower and base excess was higher in the vaginal group.…”
Section: The Problemmentioning
confidence: 99%
“…This is probably a misconception. Luterkort and Marsál have examined this issue and compared the outcome for breech babies, not only within groups of mode of delivery, but also between groups of fetal presentation [2]. Indeed, when looking at breech babies delivered vaginally versus those delivered abdominally, pH levels were lower and base excess was higher in the vaginal group.…”
Section: The Problemmentioning
confidence: 99%
“…In line with previous research, we found that breech presentation was associated with acidaemia, hypercapnia and hypoxaemia, with the differences being more prominent in the umbilical artery than in the vein. Another study found that cord acid–base levels at delivery did not vary with the type of fetal presentation …”
Section: Discussionmentioning
confidence: 98%
“…In a large retrospective study of more than 10,000 singleton breech deliveries of normal infants in 86 hospitals, the benefit of Caesarean section was significantly greater for primiparae than multiparae (18). Nevertheless, two studies of 159 and 580 singleton breech deliveries did not find any significant difference in neonatal mortality (13), or pH in the umbilical cord vein between primiparae and multiparae (19).…”
Section: Discussionmentioning
confidence: 98%